Efficacy of a prototype vaccine for caseous lymphadenitis disease in goats - Mohammed Saleh, Wessam Monther (2016)
Corynebacterium pseudotuberculosis is bacterium responsible for caseous lymphadenitis (CLA), a disease characterized by the formation of suppurative abscesses, particularly in superficial and internal lymph nodes within almost all internal organs of sheep, goats and other species including human. Due to the chronic and subclinical nature of CLA, its control is difficult and hence records a high worldwide prevalence with significant economic impact. In Malaysia, CLA is a potential threat to the livestock industry, details of the immune responses against C. pseudotuberculosis infection are not completely understood and effective vaccine is still lacking. This study was conducted using a local Malaysian C. pseudotuberculosis isolate, a murine and caprine experimental model testing the capacity of two concentrations of a prototype vaccine to protect mice and goats against experimental challenge with C. pseudotuberculosis were determined. Forty healthy female mice, aged between 3-4 weeks and weight between 15.5-20g were randomly divided in to four equal groups consisting of 10 mice each, designated groups A, B, C and D. Mice in groups A and B were inoculated intraperitoneally with 200μl of the prepared 0.5%, 1% formalin-killed vaccine of local C. pseudotuberculosis strain respectively. Groups C and D were kept as positive and negative control respectively, and inoculated intraperitoneally only with 200μl of PBS pH 7.4. Booster doses were inoculated to the mice in groups A and B after 21 days of the initial doses. Week 6th of post inoculation of the first vaccination dose; mice in all groups except negative control group were inoculated intraperitoneally with 200μl of virulent type of C. pseudotuberculosis 106 CFU per mice and were observed. All mice were euthanized at day 10 post challenged, and post mortem examination were carried on the liver, lungs, heart, kidneys, spleen and lymph nodes, while tissue samples of same organs were fixed for histopathological examination and further cultured on blood agar for bacterial isolation and identification. For goat model, 24 adult female goats aged between 11-13 months, weighing 23-30 kg, with no history of vaccination against CLA were randomly divided into 4 groups consisting of 6 goats each as A, B, C and D. Goats in groups A and B were vaccinated, respectively, with 1 ml intramuscular injection of the 0.5% and 1% formalin-killed C. pseudotuberculosis vaccine. Groups C and D were kept, respectively, as positive and negative control, and inoculated intramuscularly only with 1 ml of oil-in-water emulsion adjuvant. Booster dose was inoculated after 21 of the initial treatment. 2 weeks of post-booster dose, the goats (except in group D) were challenged with 2ml of 106 CFU of wild isolate of C. pseudotuberculosis subcutaneously. They were monitored for the entire experiment for clinical signs, and blood samples were collected at predetermined intervals into plain and EDTA tubes for IgM, IgG, IgA, Haptoglobin, Serum Amyloid A and hematology analysis. At the end of the study, the goats were sacrificed and post mortem were carried out and samples such as external and internal lymph nodes, liver, lungs, heart, kidneys, spleen, intestine, spinal cord and brain were collected for histopathological examination and for bacterial isolation and identification. Mice in group C which were inoculated only with C. pseudotuberculosis showed significant (P<0.05) changes of clinical signs. Moderate to severe ruffled fur, reduced rate of movement, decreased responsiveness and ocular discharge were observed. Signs such as huddling together, dejection, loss of appetite, pasty feces and respiratory distress were also recorded. In post mortem examination, congestion and abscesses in the site of inoculation, spleen, liver and kidneys were recorded in group C only. Microscopic examination of infected group showed significant (P< 0.05) moderate to severe hemorrhage and congestion in all organs, mild to moderate inflammatory cell infiltration and degeneration, multiple abscesses with higher scoring of necrosis and less to mild edema were observed in all organs. In contrast, the results of the vaccinated mice with CLA vaccine showed normal tissues with non-significant histopathological changes. Corynebacterium pseudotuberculosis was detected by PCR from most visceral organs and lymph nodes of 9 mice (90%) in control positive group; one mouse was found clear of infection, while it was detected only from 30% and 20% of mice in groups A and B respectively. For the goat experiment, positive control animals (group C) showed significant clinical symptoms compared to vaccinated groups that observed one week post-bacterial inoculation such as significant raise in body temperature, respiratory and heart rates and sharply decreased in rumen motility. Poor hair coat condition, decrease in body condition scoring and significant enlargement and ruptured of injection sites after 2 to 3 weeks of challenges were also observed. Moreover, a marked enlargement and occasional rupture of the affected lymph nodes were recorded in positive control group 5 to 6 weeks post challenged with C. pseudotuberculosis. Slight enlargement of regional lymph nodes near the site bacterial challenged of only 1 goat (16%) in each group A and B was observed. Both groups exposed to our formulated vaccines (groups A and B) induced significant (for both vaccines) elevations in serum Haptoglobin (Hp) and plasma serum amyloid A (SAA) concentrations which increased after 2, 5, 6 and 7 weeks when compared to non-vaccinated healthy animals of the same conditions. Hp and SAA levels in goats, which had never been exposed to vaccine, were elevated significantly one week after exposure to wild bacteria and maintained sharp increase for the interval of the evaluation. The concentration of serum IgM was found to be significantly increased at week 3 of the exposure to the first dose of vaccination, where 7 and 9-fold increases were observed in groups A and B respectively. Sharp increase up to 18 and 17-fold were observed one week after challenged with viable bacteria in groups A and B respectively. The levels for the IgM response in group C were significantly higher than the uninfected control goats (group D). The highest concentrations of IgG in group A and B (156.63 ± 2.17 ng/mL) and (164.03 ± 2.92 ng/mL) were observed after two weeks post-exposure to whole viable bacteria, respectively. For Group C, IgG mean concentration reached the maximum level (138.58 ± 1.34 ng/mL) one month after the exposure to whole viable bacteria. However the mean concentration of IgG in the vaccinated groups continued to rise following the primary and secondary vaccination. The goats vaccinated by both the formulated vaccines had no significant elevation of IgA concentration throughout the study period. In contrast, a marked increase of serum IgA levels was observed in group C during the period between 7 to 14 days post infection with viable C. pseudotuberculosis. However, only 1.2 and 1.3-fold increases were recorded in group C respectively at weeks 6 and 7. Post mortem examination of vaccinated groups revealed no significant gross pathological changes in visceral organs and also in the internal and external lymph nodes. On the other hand, high rate of gross pathological changes were recorded in all goats of positive control group. No significant gross pathological changes were observed in the brain and spinal cord of goats in group C. In the visceral organs such as lungs, liver, kidneys, spleen and heart the main gross pathological lesions observed were congestion, hemorrhage, focal areas of necrosis, fatty atrophy and abscessation. Abscess formation was rarely observed in group C except in the few organs such as the liver and lungs. In the case of lymph nodes, high percentages of abscess formation of different sizes were observed in all goats in group C. In contrast, both vaccinated groups did not develop any abscess in the lymph nodes or the visceral organs even though slight enlargements of the lymph nodes were recorded in two goats (16%) only. The histopathological changes which were observed in the positive group include edema, congestion, infiltration of inflammatory cells mainly lymphocytes and macrophages, hemorrhages, degeneration, granulomatous inflammation and caseous necrosis unlike vaccinated goats which showed significant functional hyperplasia in lymphoid tissues without histopathological changes. In the hematology, there was a statistical significant decline (P < 0.05) in Hb concentration, RBC count, MCV value and PCV in group C after exposure to viable bacteria cells. Parallel to that, statistically non-significant elevations (P > 0.05) have been observed MCHC in the same group. The WBC counts were the highest during the experimental infection of non-vaccinated goats (group C) compared with those pre-vaccinated groups (A and B). The highest stimulation in segmented neutrophil was reached 7 days post-challenge to live bacteria, when the numbers were (12.55± 1.05 ˣ109/L) in positive control group, (10.93 ±1.55 ˣ109/L) and (10.14 ±1.38 ˣ109/L) in groups A and B respectively, when compared to (8.23 ± 0.46 ˣ109) the untreated group (group D). A significant increase (p<0.05) of bands neutrophils count (0.83±0.17 ˣ109/L) was detected in positive control group after inoculation of C. pseudotuberculosis, whereas no significant change was recorded in groups A (0.49±0.09 ˣ109/L), B (0.51±0.13 ˣ109/L) and D (0.30±0.01 ˣ109/L) in the same period. The monocytes, eosinophil and basophiles counts and plasma proteins levels in all blood samples were within the normal range. Nevertheless, no significant change was recorded on the CBC values of both vaccinated groups. The findings of the PCR showed that five goats (84%) of the six animals in groups A and B pre-exposed to 0.5 % and 1.0% formalin-killed C. pseudotuberculosis remained negative. Significantly lower spreading of C. pseudotuberculosis DNA was detected in the organs and lymph nodes of the vaccinated groups. The percentage of detection in investigated tissues was found to be 100% in group C. In conclusion, following experimental challenge with wild type C. pseudotuberculosis local isolate, the formalin-killed vaccines were observed to confer statistically significant protection against infection and appeared to significantly restrict the dissemination of challenged bacteria beyond the inoculation site in the 84% of goats. Vaccinated mice (groups A, B) developed humoral immunity and produced 70% and 80% protection respectively against the disease. Moreover, only 16% of the goats immunized with this vaccine manifested mild clinical and pathological infection thus, a potentially important route of disease transmission was eliminated. The results of this study provide information pertinent to the development of an effective caseous lymphadenitis eradication vaccination strategy in Malaysia.